Profil Darah dan Gambaran Makroskopis Kesembuhan Luka Tikus Wistar (Rattus norvegicus) Infeksi Staphylococcus aureus yang Diberi Ekstrak Bawang Merah (Allium cepa L.) - Rosyadi, Imron; Alhidayany, Desriza; S, Christin Marganingsih (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Wound is one of the most common cases happened frequently. Infected wound by pathogenic microorganism could inhibit wound healing process. The microorganism that often infect the wound is Staphylococcus aureus. Shallot had believed as one of traditional medicine that believes as an alternative therapy for wound healing. This study aimed to determine the blood profile and macroscopic images of wound healing in Wistar rats (Rattus norvegicus) infected by Staphylococcus aureus and given shallot extract (Allium cepa L.). This study used 12 rats, aged about 2 months and weighed 180-250 gram is divided into 4 groups, each group consist of 3 rats. Rats were injured by incision wound at 1 cm length and ± 2 mm depth, then infected by Staphylococcus aureus bacteria. Group I and II were droped of shallot extract 40% and 80%, while Group III was droped by povidon iodine 10%, and Group IV was given nothing (control group) until the wound healed. Research observation was did at day-0, 7, 14, and 21. The length of wound was measured in centimeter evere week and blood sampling were done at day-0 and day-21. The observational data of wound length were analysis using Friedman, Wilcoxon, dan Mann-Whitney. The result of research showed the wound length average on day-7 in Group I: 0,733 cm; Group II: 0,433 cm; Group III: 0,567 cm; and Group IV: 0,767 cm (p<0,05). The wound length average on day-14 in Group I: 0,433 cm and Group IV: 0,333 cm (p>0,05), Group II and III were healed (p>0,05). In day-21 all wound were completely healed. The rats blood profile on day-0 and day-21 showed that erythrocytes total count, hemoglobin (Hb), and packed cell volume (PCV) were in normal range. Rats were in health condition. Thus it could be concluded that the time need for the wounds to heal in rats that were treated with shallot extract 80% is equal to rats were treated with povidon iodine 10% on the 14th day of the study while rats that were treated with shallot extract 40% is equal to rats was given nothing on the 21st day of the study. Shallot extract 80% can treat wound that infected by Staphylococcus aureus is equal to povidon iodine 10% treatment.